Ion-doped low-nickel layered oxide sodium ion battery positive electrode material and preparation method thereof

Preparation of the positive electrode material of low-nickel layered oxide sodium ion battery through high-temperature solid-phase method and ion doping technology, solving the problems of high-nickel-type materials with high cost and poor performance, and achieving low cost, high capacity and good cycle stability Battery performance.

CN119297267APending Publication Date: 2025-01-10SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411602689.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing high-nickel sodium ion battery layered oxide cathode materials have problems such as high cost, fast capacity attenuation and poor circulation performance, and require a low-cost and excellent performance alternative material.

Method used

The positive electrode material of ion-doped low-nickel layered oxide sodium ion battery is prepared by high-temperature solid phase method. Through segmented sintering and ion doping technologies, the crystal structure and electrochemical performance of the material are optimized. The specific steps include ball milling mixing and segmented sintering. and grinding, ball milling and sintering of stoichiometric ratios were performed using sodium sources, nickel-ferromanganese hydroxides, calcium sources, lithium sources, magnesium sources and dispersants.

Benefits of technology

It achieves low cost, low strain, high capacity and good cycle stability, extends the cycle life of the battery, and improves the storage capacity and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297267A_ABST
    Figure CN119297267A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and discloses a preparation method of an ion-doped low-nickel layered oxide sodium ion battery positive electrode material. The chemical formula of the sodium ion battery positive electrode material is Na < 0.95-x > Ca < x > (Ni < 0.2 > Fe < 0.4 > Mn < 0.4 >) < 1-y-z > Li < y > Mg < z > O < 2 >. The preparation method comprises the following steps: weighing a sodium source, a nickel-iron-manganese hydroxide, a calcium source, a lithium source, a magnesium source and a certain amount of a dispersing agent in a ball-milling tank, and carrying out ball-milling mixing to obtain a sodium-ion battery positive electrode material precursor; and placing the sodium ion battery positive electrode material precursor in a corundum crucible, transferring the corundum crucible to a box-type atmosphere furnace for segmented sintering, naturally cooling to room temperature after sintering is completed, and grinding and sieving to obtain the ion-doped low-nickel layered oxide sodium ion battery positive electrode material. The positive electrode material has the advantages of low cost, low strain, high capacity, good cycle stability, simple preparation process, high repeatability and great potential of large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of positive electrode materials for sodium ion batteries, and in particular relates to a method for preparing an ion-doped low-nickel layered oxide positive electrode material for sodium ion batteries. Background Art

[0002] With the rapid development of my country's new energy vehicle industry, the demand for power batteries is becoming increasingly urgent. At the same time, with the consideration of global environmental protection and energy security, the development of electrification and new energy vehicles has also received more attention. At present, lithium-ion batteries are still the mainstream power batteries, but lithium resources are limited and prices fluctuate greatly. As global lithium resource reserves gradually decrease, the development of other alternative energy sources is an inevitable trend.

[0003] As a resource-rich and low-cost battery system, sodium-ion batteries have the advantages of high safety and environmental friendliness. In the future, with the increase in global energy storage demand and the growing demand for energy storage equipment in 5G communications, electric vehicles, renewable energy and other fields, sodium-ion batteries are expected to become one of the most widely used and most promising technologies in the field of energy storage equipment.

[0004] As an important component of sodium-ion batteries, the electrochemical properties of positive electrode materials have a very important influence on the various performances of batteries. High-nickel sodium-ion battery layered oxide positive electrode materials have the advantages of high energy density, high capacity and long life, and have become one of the current research hotspots in the field of new energy. However, the price of nickel salts on the market is very expensive, which greatly increases the cost of manufacturing positive electrode materials, and there are still some problems with high-nickel sodium-ion battery layered oxide positive electrode materials, such as rapid capacity decay and poor cycle performance. Therefore, it is particularly urgent to reduce production and preparation costs and optimize the electrochemical properties of materials. For this reason, researchers are constantly exploring new preparation methods, such as reducing nickel content, doping, coating and other means. With the continuous deepening of research, low-cost and high-performance sodium-ion battery positive electrode materials will play an important role in the future new energy field. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material, which has low cost, low strain, high capacity and good cycle stability, simple preparation process, high repeatability and great potential for large-scale production.

[0006] In order to solve the problem raised by the technical background, the present invention provides the following technical solutions:

[0007] A method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material, wherein the positive electrode material has a chemical formula of Na 0.95-x Ca x (Ni 0.2 Fe0.4 Mn 0.4 ) 1-y-z Li y Mg z O2, where 0≤x≤0.1, 0≤y≤0.1, 0≤z≤0.1, and the charge balance is satisfied between the elements in the chemical formula.

[0008] A method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material, which is prepared by a high-temperature solid phase method, specifically comprising the following steps:

[0009] S1: According to the stoichiometric ratio of the above chemical formula, a sodium source, nickel iron manganese hydroxide, a calcium source, a lithium source, a magnesium source and a certain amount of a dispersant are weighed in a ball mill, and ball milled to obtain a precursor of a positive electrode material for a sodium ion battery.

[0010] S2: placing the sodium ion battery positive electrode material precursor obtained in step S1 in a corundum crucible, and then transferring it to a box-type atmosphere furnace for segmented sintering. After the sintering is completed, naturally cooling it to room temperature, grinding and sieving it to obtain a layered oxide sodium ion battery positive electrode material.

[0011] Furthermore, the nickel-iron-manganese hydroxide in step S1 has a structural formula of Ni 0.2 Fe 0.4 Mn 0.4 (OH)2.

[0012] Furthermore, the sodium source in step S1 is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium phosphate, sodium nitrate, sodium oxide and sodium citrate.

[0013] Furthermore, the calcium source in step S1 is one or more of calcium gluconate, calcium chloride, calcium lactate, calcium carbonate, calcium acetate, calcium oxide, calcium hydrogen phosphate, calcium hydrogen carbonate, calcium bromide and calcium iodide.

[0014] Furthermore, the lithium source in step S1 is one or more of lithium oxide, lithium carbonate, lithium chloride, lithium peroxide, lithium phosphate and lithium sulfate.

[0015] Furthermore, the magnesium source in step S1 is one or more of magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium oxide, magnesium hydroxide, magnesium nitrate and magnesium bromide.

[0016] Furthermore, the dispersant in step S1 is one or more of polyethylene glycol-4000 (PEG-4000), polyethylene glycol-6000 (PEG-6000), and polyvinyl pyrrolidone (PVP).

[0017] Furthermore, the amount of the dispersant used in step S1 is 0.5-2 wt % of the total mass of the sodium source, nickel iron manganese hydroxide, calcium source, lithium source and magnesium source.

[0018] Furthermore, in step S1, the ball-to-material ratio of the ball milling is 1:2-10; the ball milling speed is set to 200-400 r / min, and the ball milling time is 0.5-2 h.

[0019] Furthermore, the sintering atmosphere of the box-type atmosphere furnace in step S2 is oxygen or air; the sintering temperature of the first stage of the staged sintering is set to 300-500°C, and the insulation time is 2-5h; the sintering temperature of the second stage is set to 700-900°C, the insulation time is 10-24h, and the heating rate is set to 2-5°C / min.

[0020] Compared with the prior art, the method for preparing a layered oxide sodium ion battery positive electrode material of the present invention has the following advantages:

[0021] 1. Through segmented sintering, the crystal structure of the material can be optimized and Na + storage space, thereby improving the storage capacity of the material; segmented sintering helps to reduce defects and stress in the material during the sintering process, making the material have a more stable crystal structure; segmented sintering can reduce the volume change caused by interlayer slip and phase change during the charge and discharge process of the material, thereby extending the cycle life of the battery.

[0022] 2. Due to Li + The ionic radius is The ionic radius of Li is close to that of Ni, Fe and Mn. + The doping mainly occupies the octahedral position of the TM layer. + The introduction of can smooth the charge and discharge curves, effectively eliminate vacancy order, and inhibit material phase change, thereby significantly improving rate performance and cycle stability.

[0023] Mg also has similar valence and ionic radius as Ni, Fe, and Mn, so 2+ Usually occupy the transition metal layer, inhibiting the phase change and Na + / Vacancy order, resulting in excellent reversible capacity and long cycle stability.

[0024] and With similar ionic radius, calcium ion doping will mainly occupy the position of sodium ions. 2+ The introduction of will expand the alkali metal layer distance of the material, thus facilitating the Na + diffusion, thereby improving the cyclic stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1This is a SEM image of the ion-doped low-nickel layered oxide sodium ion battery positive electrode material obtained in Example 2;

[0026] Figure 2 This is a SEM image of the low-nickel layered oxide sodium ion battery positive electrode material obtained in Comparative Example 4;

[0027] Figure 3 The first charge and discharge curves of Example 2 and Comparative Example 4 at a rate of 0.1C are shown;

[0028] Figure 4 It is the cycle performance diagram of Example 2 and Comparative Example 4 at 1.0C rate. DETAILED DESCRIPTION

[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments in this application can be combined with each other. In order to further understand the present invention, the present invention is further described below in conjunction with the specification and specific preferred embodiments, and these embodiments cannot be understood as limiting the scope of protection claimed in this application.

[0030] The method in the following embodiments is:

[0031] A method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material, which is prepared by a high-temperature solid phase method, specifically comprising the following steps:

[0032] S1: According to the stoichiometric ratio of the above chemical formula, a sodium source, nickel iron manganese hydroxide, a calcium source, a lithium source, a magnesium source and a certain amount of a dispersant are weighed in a ball mill, and ball milled to obtain a precursor of a positive electrode material for a sodium ion battery.

[0033] S2: placing the sodium ion battery positive electrode material precursor obtained in step S1 in a corundum crucible, and then transferring it to a box-type atmosphere furnace for segmented sintering. After the sintering is completed, naturally cooling it to room temperature, grinding and sieving it to obtain a layered oxide sodium ion battery positive electrode material.

[0034] In step S1, the nickel-iron-manganese hydroxide has a structural formula of Ni 0.2 Fe 0.4 Mn 0.4 (OH)2.

[0035] In step S1, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium phosphate, sodium nitrate, sodium oxide and sodium citrate.

[0036] The calcium source is one or more of calcium gluconate, calcium chloride, calcium lactate, calcium carbonate, calcium acetate, calcium oxide, calcium hydrogen phosphate, calcium hydrogen carbonate, calcium bromide and calcium iodide.

[0037] In step S1, the lithium source is one or more of lithium oxide, lithium carbonate, lithium chloride, lithium peroxide, lithium phosphate and lithium sulfate.

[0038] In step S1, the magnesium source is one or more of magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium oxide, magnesium hydroxide, magnesium nitrate and magnesium bromide.

[0039] In step S1, the dispersant is one or more of polyethylene glycol-4000 (PEG-4000), polyethylene glycol-6000 (PEG-6000), and polyvinyl pyrrolidone (PVP).

[0040] Example 1

[0041] Sodium carbonate, Ni 0.2 Fe 0.4 Mn 0.4 The (OH)2 precursor, lithium oxide and magnesium oxide are weighed and placed in a ball mill according to a stoichiometric ratio of 0.95:0.95:0.03:0.02, and polyvinyl pyrrolidone K30 is added as a dispersant at a total weight of 0.5wt% of the total material in the mill. The bead-to-material ratio in the ball mill is 3:1, the ball mill speed is set to 300r / min, the ball milling time is 1h, and then heated to 500°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 2h, and continued to rise to 850°C at a heating rate of 3°C / min, kept warm for 15h, cooled naturally, and crushed and sieved to obtain an ion-doped layered oxide sodium ion battery positive electrode material.

[0042] Performance Test:

[0043] The layered oxide sodium ion battery positive electrode material obtained above was assembled into a button cell, and the active material: conductive carbon black Super P: PVDF = 8:1:1 were weighed and mixed, and N-methylpyrrolidone solution (NMP) was added for homogenization, and the slurry was evenly coated on an aluminum foil, dried in a vacuum drying oven at 80°C for 4h, and the sodium positive electrode sheet used was obtained by rolling and cutting (14mm). A metal sodium sheet was used as a counter electrode, a 1 mol / L NaClO4 ethylene carbonate (EC) / propylene carbonate (PC) (volume ratio 1:1) solution was used as an electrolyte, and glass fiber was used as a diaphragm. The button half-cell was assembled in an argon-filled glove box.

[0044] Example 2

[0045] Sodium carbonate, calcium acetate, Ni 0.2 Fe 0.4 Mn 0.4The (OH)2 precursor, lithium oxide and magnesium oxide are weighed and placed in a ball mill according to a stoichiometric ratio of 0.93:0.02:0.95:0.03:0.02, and polyvinyl pyrrolidone K30 is added as a dispersant at a total weight of 0.5wt% of the total material in the mill. The bead-to-material ratio in the ball mill is 3:1, the ball mill speed is set to 300r / min, the ball milling time is 1h, and then heated to 500°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 2h, and continued to rise to 850°C at a heating rate of 3°C / min, kept warm for 15h, cooled naturally, and crushed and sieved to obtain an ion-doped layered oxide sodium ion battery positive electrode material.

[0046] like Figure 1 and Figure 2 As shown in Figure 2, the primary particle size of the doped and modified sodium ion battery cathode material is not much different, while a hollow structure appears on the surface of the secondary particles, which is beneficial to increase the specific surface area of ​​the material and thus improve the discharge capacity of the material; Figure 3 As shown in Figure 2, the modified material has improved capacity and charge / discharge voltage, which is beneficial to improving the energy density of the battery; Figure 4 As shown, at a rate of 1.0C, after 50 cycles, the discharge capacity and cycle stability of Example 2 are better than those of Comparative Example 4.

[0047] Comparative Example 1

[0048] Sodium carbonate, Ni 0.2 Fe 0.4 Mn 0.4 The (OH)2 precursor is weighed into a ball mill according to a stoichiometric ratio of 0.95:1, and polyvinyl pyrrolidone K30 is added as a dispersant at a total weight of 0.5wt% of the total material in the mill. The bead-to-material ratio in the ball mill is 3:1, the ball mill speed is set to 300r / min, the ball milling time is 1h, and then heated to 500°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 2h, and continued to rise to 800°C at a heating rate of 3°C / min, kept warm for 12h, cooled naturally, and crushed and sieved to obtain an ion-doped layered oxide sodium ion battery positive electrode material.

[0049] Comparative Example 2

[0050] Sodium carbonate, Ni 0.2 Fe 0.4 Mn 0.4The (OH)2 precursor is weighed into a ball mill according to a stoichiometric ratio of 0.95:1, and polyvinyl pyrrolidone K30 is added as a dispersant at a total weight of 0.5wt% of the total material in the mill. The bead-to-material ratio in the ball mill is 3:1, the ball mill speed is set to 300r / min, the ball milling time is 1h, and then heated to 500°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 2h, and continued to rise to 820°C at a heating rate of 3°C / min, kept warm for 12h, cooled naturally, and crushed and sieved to obtain an ion-doped layered oxide sodium ion battery positive electrode material.

[0051] Comparative Example 3

[0052] Sodium carbonate, Ni 0.2 Fe 0.4 Mn 0.4 The (OH)2 precursor is weighed into a ball mill according to a stoichiometric ratio of 0.95:1, and polyvinyl pyrrolidone K30 is added as a dispersant at a total weight of 0.5wt% of the total material in the mill. The bead-to-material ratio in the ball mill is 3:1, the ball mill speed is set to 300r / min, the ball milling time is 1h, and then heated to 500°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 2h, and continued to rise to 850°C at a heating rate of 3°C / min, kept warm for 12h, cooled naturally, and crushed and sieved to obtain an ion-doped layered oxide sodium ion battery positive electrode material.

[0053] Comparative Example 4

[0054] Sodium carbonate, Ni 0.2 Fe 0.4 Mn 0.4 The (OH)2 precursor is weighed into a ball mill according to a stoichiometric ratio of 0.95:1, and polyvinyl pyrrolidone K30 is added as a dispersant at a total weight of 0.5wt% of the total material in the mill. The bead-to-material ratio in the ball mill is 3:1, the ball mill speed is set to 300r / min, the ball milling time is 1h, and then heated to 500°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 2h, and continued to rise to 850°C at a heating rate of 3°C / min, kept warm for 15h, cooled naturally, and crushed and sieved to obtain an ion-doped layered oxide sodium ion battery positive electrode material.

[0055] The experimental results are recorded in Table 1 below:

[0056] Table 1

[0057]

[0058] It can be seen from Table 1 that the discharge capacity of Comparative Example 4 shows a gradual increase compared with Comparative Examples 1 to 3. This is because the sintering temperature and holding time are increased, thereby increasing the crystallinity of the material, improving the microstructure of the material, and thus improving the density and uniformity of the material; increasing the sintering temperature and time can also optimize the performance indicators such as the conductivity and dielectric constant of the material, thereby improving its discharge capacity. It can be seen from the embodiments and comparative examples that ion doping is beneficial to significantly improve the discharge capacity of the material, indicating that ion doping is beneficial to inhibiting the phase change and Na+ phase transition of the material during the charge and discharge process. + / vacancies are ordered, thus improving its electrochemical performance.

[0059] It should be understood that the above detailed description of the technical solution of the present invention with the help of optimized embodiments is illustrative rather than restrictive, and it cannot be determined that the specific implementation methods of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, modifications to the technical solutions recorded in the embodiments, or equivalent replacement of some of the technical features therein, should be deemed to fall within the scope of patent protection determined by the claims submitted for the present invention.

[0060] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An ion-doped low-nickel layered oxide sodium ion battery positive electrode material, characterized in that: The chemical formula of the positive electrode material is Na 0.95-x Ca x (Ni 0.2 Fe 0.4 Mn 0.4 ) 1-y-z Li y Mg z O2, where 0≤x≤0.1, 0≤y≤0.1, 0≤z≤0.1, and the charge balance between the elements in the chemical formula is satisfied.

2. The method for preparing the ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 1, characterized in that: The high temperature solid phase method is used to prepare the product, which specifically includes the following steps: S1: weighing a sodium source, nickel iron manganese hydroxide, a calcium source, a lithium source, a magnesium source and a dispersant in a ball mill according to a stoichiometric ratio, and performing ball milling to mix to obtain a precursor of a positive electrode material for a sodium ion battery; S2: placing the sodium ion battery positive electrode material precursor obtained in step S1 in a corundum crucible, and then transferring it to a box-type atmosphere furnace for segmented sintering. After the sintering is completed, naturally cooling it to room temperature, grinding and sieving to obtain an ion-doped low-nickel layered oxide sodium ion battery positive electrode material.

3. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the nickel-iron-manganese hydroxide has a structural formula of Ni 0.2 Fe 0.4 Mn 0.4 (OH)2.

4. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium phosphate, sodium nitrate, sodium oxide and sodium citrate.

5. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the calcium source is one or more of calcium gluconate, calcium chloride, calcium lactate, calcium carbonate, calcium acetate, calcium oxide, calcium hydrogen phosphate, calcium hydrogen carbonate, calcium bromide and calcium iodide.

6. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the lithium source is one or more of lithium oxide, lithium carbonate, lithium chloride, lithium peroxide, lithium phosphate and lithium sulfate.

7. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the magnesium source is one or more of magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium oxide, magnesium hydroxide, magnesium nitrate and magnesium bromide.

8. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the dispersant is one or more of polyethylene glycol-4000 (PEG-4000), polyethylene glycol-6000 (PEG-6000), and polyvinyl pyrrolidone (PVP); the amount of the dispersant is 0.5wt% to 2wt% of the total mass of the sodium source, nickel-iron-manganese hydroxide, calcium source, lithium source, and magnesium source.

9. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the ball-to-material ratio of the ball milling is 1:2-10; the ball milling speed is set to 200-400 r / min, and the ball milling time is 0.5-2 h.

10. The method for preparing an ion-doped low-nickel layered oxide sodium ion battery positive electrode material according to claim 2, characterized in that: The sintering atmosphere of the box-type atmosphere furnace in step S2 is oxygen or air; the sintering temperature of the first stage of the staged sintering is set to 300-500°C, and the insulation time is 2-5h; the sintering temperature of the second stage is set to 700-900°C, the insulation time is 10-24h, and the heating rate is set to 2-5°C / min.

Citation Information

Patent Citations

  • Metal ion doped modified sodium ion material as well as preparation method and application thereof

    CN114005969A

  • Low-nickel high-energy-density layered sodium ion battery positive electrode material and preparation method thereof

    CN117012949A

  • Sodium-ion battery concentration gradient oxide positive electrode material and preparation method and application thereof

    CN118145718A

  • Mono-crystalline Cathode Material for Sodium-ion Battery and Preparation Method and Application Thereof

    US20240021807A1

Cited By

  • Preparation method and application of sodium ion layered oxide cathode material nickel iron sodium manganate

    CN119637955A